An eight year prospective study of outcome prediction by antiperinuclear factor and antikeratin antibodies at onset of rheumatoid arthritis. Issue 8 (1st August 2002) - Genevay, S; Hayem, G; Verpillat, P; Meyer, O
Abstract : Objectives: Antikeratin antibodies (AKA) and antiperinuclear factor (APF) are specific antibodies found very early in rheumatoid arthritis (RA). The objective of this eight year follow up study was to assess the value of early AKA and APF assays in predicting functional disability and cartilage damage. Method: In 2000, 64 patients tested for AKA and APF (antifilaggrin antibodies) between 1990 and 1993 during evaluation of early symmetric oligoarthritis or polyarthritis (suspected RA) were invited to participate in this non-concurrent cohort study. The Health Assessment Questionnaire (HAQ) score, disease activity score (DAS), and Larsen radiographic score were the primary evaluation criteria. Results: Twenty nine patients were re-evaluated. Clinical and laboratory data obtained in 1993 were similar in this group and in the 35 other patients. Twenty five patients had received a diagnosis of RA. Nine (31%) were rheumatoid factor (RF) positive, nine (31%) were AKA positive, and six (21%) were APF positive during the first year of the disease. APF was correlated with the Larsen score (p=0.011) and DAS (p=0.035) evaluated after a mean disease duration of 8.55 years. All APF positive patients had erosive disease. AKA was correlated with the DAS (p=0.035). Conclusion: The presence of AKA or APF early in the course of RA was associated with the DAS or Larsen score eight years later. The number of patients was small, but the findings confirmed those of studies with shorter follow ups. Antifilaggrin antibodies should be included in the initial investigation of patients with RA and, when positive, should alert to a high risk of poor outcomes.